Information flow and acquisition of knowledge in water governance in the Upper East Region of Ghana - Schiffer, Eva; McCarthy, Nancy; Birner, Regina; Waale, Douglas; Asante, Felix Ankomah (International Food Policy Research Institute, 2008)
This paper provides an assessment of information flows and the acquisition of knowledge in water governance of the Upper East Region, Ghana. These flows are patchy, often parallel, disconnected or slow. In many cases a great deal of information is gathered but for a number of reasons not transferred into knowledge that impacts on decision making and action. An analysis of knowledge flows can serve as guidance for research projects and capacity building endeavours to allow tackling the gap between data collection and knowledge for action.